Development, implementation, and evaluation of an innovative clinical trial operations training program for Africa (ClinOps) - Dawit Asmamaw Ejigu; Abebaw Fekadu; Jeremy Whitty; Tsegahun Manyazewal; Pamela Nebeta; Almari Conradie; Brenda Okech; Alice Neequaye; Sinéad Whitty; Jennifer Lehrman; Renee Holt; Rahel Birhane; et al. (BMC Medical Education)
Abstract Background Africa’s involvement in clinical trials remains very low. Although the crucial role of training initiatives in building clinical trial capacity in Africa has been documented, current efforts fall short as they lack alignment with local contexts. This study aimed to design, develop, implement, and evaluate an innovative clinical trial operations training program for Africa. Methods We developed ClinOps, a novel 10-week clinical trial operations training program for study coordinators in Africa to enhance their expertise in four fundamental areas: designing, conducting, managing, and reporting clinical trials. To streamline the learning process, we used cloud-based applications that minimize the need for software installations while maximizing student engagement. VoiceThread facilitated interactive content that could be accessed offline. Moodle, an open-source learning management system, offered a platform for sharing learning tools, mentorship, and rubric-driven competency assessments, including quizzes, forums, tutorials, and group assignments. We utilized Zoom for live tutorials and mentoring as required. Effectiveness of the program was evaluated through quantitative pre- and post-surveys, qualitative end-course evaluations, and a comprehensive monitoring and evaluation framework. The pre- and post-surveys measured changes in trainees’ confidence in clinical trial domains and leadership and coordination skills. End-course evaluations gathered feedback on the course content, organization, technology, and instructional methods. We used Wilcoxon rank test to analyze pre- and post-survey scores and thematic analysis to analyze the qualitative data. Results In the initial cohort, 88 study coordinators from 19 countries participated, including 56 (64%) females, with 57 (65%) actively employed as study coordinators during the training, and 85 (97%) possessing prior experience in clinical trial roles. Among these, 71 (81%) successfully completed the course, with 69 (97%) also completing the post-course assessment. Post-training scores demonstrated substantial improvement compared to pre-training scores in each competency area, including in designing (pre-post training median score = 3.6 vs. 4.6, median difference = 1.0, 95% CI 0.8–1.1, p < 0.001), managing (pre-posttest median score = 3.4 vs. 4.2, median difference = 0.6, 95% CI 0.4–0.8, p < 0.001), conducting (pre-post training median score = 3.9 vs. 4.7, median difference = 0.9, 95% CI 0.6-1.0, p < 0.001), and reporting (pre-posttest median score = 3.0 vs. 4.5, median difference = 1.0, 95% CI 0.9–1.5, p < 0.001) clinical trials. The monitoring and evaluation data confirm the program’s adherence to training best practices, including alignment with local priorities, country ownership, pedagogic innovation, institutional capacity building, sustainability, and ongoing partnerships. The end-course evaluation reflects participants’ positive feedback on the program’s structure, content, relevance to their current roles, and overall delivery methods. Conclusion The ClinOps program, designed by experts from academia and product development partners, enhanced participants’ clinical trial competencies. To effectively build clinical trials capacity on the continent, training programs should provide thorough competency development in designing, conducting, managing, and reporting trials.